Correlation between Interleukin-6 (IL-6), High Sensitivity C-Reactive Protein (hsCRP), Endothelin-1 (ET-1), Asymmetric Dimethylarginine (ADMA) and Insulin Resistance (HOMA-IR) in Central Obese Men - Andri Hidayat; Andi Wijaya; Harun Alrasyid (The Indonesian Biomedical Journal, 2011)
BACKGROUND: Many studies have shown that obesity was closely related to insulin resistance via several pathways such as inflammation, oxidative stress, lipolysis, and endothelial dysfunction. This study was carried out to observe the correlation between inflammation (IL-6 and hsCRP), lipolysis process (ET-1), and endothelial dysfunction (ADMA) and insulin resistance (HOMA-IR) in centrally obese men.METHODS: This was a cross sectional study on 62 male subjects aged 30–60 years old with waist circumference (WC) >90 cm. IL-6, ET-1 and ADMA levels were measured using ELISA method, while hsCRP and insulin were measured using chemiluminescence method. All blood testings were conducted in Prodia Clinical Laboratory.RESULTS: The results showed that WC was significantly correlated with hsCRP (r=0.294, p=0.022 ), ET-1 (r=0.257, p=0.047 ) and ADMA (r=0.338, p=0.009). We also found a significant correlation between hsCRP with HOMA-IR (r=0.324, p=0.021), ADMA with HOMA-IR (r=0.280, p=0.045), and IL-6 with hsCRP (r=0.437, p=0.003).CONCLUSIONS: hsCRP and ADMA have significant correlation with HOMA-IR in centrally obese men. HOMA-IR significantly increases in subjects with ADMA above median and either IL-6 or hsCRP above median, as compared to those in the other groups. Inflammation and endothelial dysfunction are important causal pathways of insulin resistance state in centrally obese men.KEYWORDS: obesity, IL-6, hsCRP, ET-1, ADMA, HOMA-IR